Screening system for heart valve disease - Mohd Zubir Bin Suboh (School of Mechatronic Engineering, 2011)
The problems that motivate this study are limitation of heart sound auscultation technique, lack of intelligence utilization in phonocardiograph instrument, unavailability of advance diagnostic equipments and necessity of robust and reliable technique in signal processing.